L'evoluzione della codifica del genitivo dal tipo sintetico al tipo analitico nelle carte del Codice diplomatico longobardo - Cecilia Valentini (Premio Ricerca «Città di Firenze», 2018)
The subject of this work is the morphosyntactic analysis of a corpus of Latin documentary papers which were written in the centre and the north of the Italian peninsula between the 7th and the 8th century. The study focuses on the competition, in the nominal phrase, between synthetic and analytical encoding of the dependent name, which is the result of the grammaticalization process of the phrase starting by the preposition "de", which in the Romance phase replaced the genitive case. This change is interpreted on a semantic basis, making use of the functional domain of possession. The volume also analyses nominal morphology which, although characterized by polymorphism and inconsistency, manifests phenomena such as the levelling of random oppositions and the reconstruction of inflectional paradigms, two inverse processes which find their cause in the principle of animacy.